The "Prevent Anemia" Board Game Increases Adolescent Knowledge - Ade Devriany; Fitri Suci Ramadani; Wirawati Amin; Suriani (Napande: Jurnal Bidan, 2026)
Background: Anemia remains a public health problem among adolescent girls, primarily due to low iron intake and non-compliance with iron supplementation (IBP). Anemia in adolescent girls can impact learning concentration, academic achievement, and fitness, and is at risk of continuing into pregnancy. One important factor influencing anemia prevention behavior is knowledge. The prevalence of iron supplementation among adolescent girls in South Sulawesi in 2023 was 65.5% and in Jeneponto Regency it was 73.0%, still below the national target of 75.0%. Therefore, innovative, engaging, and easily understood educational media are needed for adolescents, one of which is through board-based educational games. Interactive approaches are considered capable of increasing engagement, motivation, and understanding of adolescent girls' health. Methods: This study employed a quantitative method with a pre-experimental one group pre-test and post-test design. The sample consisted of 80 adolescent girls at SMPN 1 Tamalatea, Jeneponto Regency, selected using a purposive sampling technique. The research instrument was a questionnaire measuring knowledge of anemia and iron supplementation, which had been tested for validity and reliability. The intervention was delivered through health education using the “Cegah Anemia” boardgame, implemented in group-based learning sessions. Results: The findings showed that prior to the intervention, most respondents had a moderate (61.3%) or poor (37.5%) level of knowledge. After the intervention, knowledge levels increased, with the majority of respondents categorized as having good knowledge (57.5%). The Wilcoxon signed-rank test indicated a statistically significant improvement in knowledge following the intervention. Conclusion: Health education using the “Cegah Anemia” boardgame is effective in improving adolescent girls’ knowledge regarding anemia and iron supplementation at SMPN 1 Tamalatea